Hospital management: Application of the PDCA cycle as a strategy to combat COVID-19 in urgent and emergency units (Research, Society and Development, 2021)
This study aims to understand the stages of the PDCA Cycle as a coping plan for COVID-19 in Urgency and Emergency Units. It is an integrative literature review, carried out by searching for articles indexed in the Virtual Health Library (VHL). The inclusion criteria include literature review research available in the databases described, between the years 2010 to 2020. The exclusion criteria were duplicate, incomplete articles, abstracts, reviews, debates, experience reports and articles unavailable in the whole. To collect the data, 09 scientific articles and 03 studies referring to health entities were analyzed. The results show the stages of the PDCA cycle being, plan, execute, verify and act. With an emphasis on contextualizing the implementation of the PDCA cycle as a plan to reduce COVID-19 cases in urgent and emergency services, it is revealed that the lack of information from the population on when to use urgent and emergency services has been a great difficulty for professionals in times of pandemic, resulting in agglomerations in the referred units and overload of the system. We conclude that the PDCA cycle can be applicable to the most diverse types of organizations, including urgent and emergency services, making it possible to reduce the high demand of the population for highly complex services.